Diversity and Management of Useful Homegardens Plant Species in Arba Minch Town, Southern Ethiopia: Implication for Plant Diversity Conservation and Food Security - Mulugeta Kebebew (International Journal of Economic Plants)
Homegardens host a significant portion of plant biodiversity and played an important role towards the development of early agriculture and domestication of crops and fruit trees, a still ongoing process. The study was conducted on homegardens of Arba Minch town, Southern Ethiopia with the aim of documenting the indigenous knowledge on categorization, use and management of useful plants species in homegardens. A random sample of 100 homegardens from four sub-cities of Arba Minch town was used to collect useful plant species data. Techniques used were focus group discussion, semi-structured interviews, home garden tour and free listing. A total of 138 useful plant species were documented, of which 12.36% were edible plants, 11.90% income source plants, and 8.92% shade plants. Fabaceae was the dominant family represented by 17 species, followed by Euphorbiaceae with 10 species and Asteraceae and Poaceae with 6 species each. Homegarden size of the study area ranged from 220 to 1235 m2 with an average size of 727.5 m2. The age of homegarden is ranged from 10 years old to 50 years old with an average age of 30. The number of species in the homegarden ranges from 10 to 45 with the average of 27.5.  The study indicates that homegardens are contributing to food security, income generation and livelihoods in Arba Minch town through production of ornamental, food plants, fodder, medicinal, timber and construction. The study recommended that the management of useful plant species in homegardens will be scaled up and further expanded and assisted by agricultural extensions in urban areas in Ethiopia.